Physically Developed and Exploratory Young Infants Contribute to Their Own Long-Term Academic Achievement - Bornstein, Marc H.; Hahn, Chun-Shin; Suwalsky, Joan T. D. (Psychological Science, 2013)
A developmental cascade defines a longitudinal relation in which one psychological characteristic uniquely affects another psychological characteristic later in time, separately from other intrapersonal and extrapersonal factors. Here, we report results of a large-scale ( N = 374), normative, prospective, 14-year longitudinal, multivariate, multisource, controlled study of a developmental cascade from infant motor-exploratory competence at 5 months to adolescent academic achievement at 14 years, through conceptually related and age-appropriate measures of psychometric intelligence at 4 and 10 years and academic achievement at 10 years. This developmental cascade applied equally to girls and boys and was independent of children’s behavioral adjustment and social competence; mothers’ supportive caregiving, verbal intelligence, education, and parenting knowledge; and the material home environment. Infants who were more motorically mature and who explored more actively at 5 months of age achieved higher academic levels as 14-year-olds.